Perlindungan Hak Asasi Manusia dalam Konteks Pelaksanaan Hukum Pidana Pers - Zainal Arifin; Emi Puasa Handayani (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Protection of human rights (HAM) in the context of implementing press criminal law is a crucial issue that is developing along with the dynamics of development in society and technology. The existence of mass media as a means of information that has great influence is the focus in fulfilling and protecting human rights. Based on this background, this research questions three things, namely, first, what is the mechanism for applying criminal law in the context of mass media reporting. Second, what is the impact of criminal law policy on the protection of human rights in the practice of implementing criminal law. Third, what is the role of press freedom and media responsibilities in determining the boundaries between information protection and human rights protection. The method used is normative legal research, which involves collecting and analyzing legal data related to press criminal law regulations and policies. The main data sources include primary legal materials, such as statutory regulations, court decisions, and related laws and regulations. Apart from that, secondary data sources in the form of legal literature, scientific articles, and expert views are also used to strengthen the analysis. With this approach, it is hoped that this research can contribute to understanding the complexity of the relationship between press criminal law, human rights, and the dynamics of mass media in the context of press freedom and its responsibilities.